2017
DOI: 10.1007/s00405-017-4648-y
|View full text |Cite
|
Sign up to set email alerts
|

The treatment for the first branchial cleft anomalies in children

Abstract: The objective of this study is to make a clinical analysis for first branchial cleft anomalies (FBCAs), especially introduce the relationship between the Type I/II FBCA with the facial nerve and to demonstrate the importance of using intraoperative microscope and facial nerve monitoring. This is a retrospective review of patients with FBCAs treated in Beijing Children's Hospital, from Jan 2013 to Dec 2015. Clinical data of patients, including sex, age, chief complains, history of surgery, incision and drainage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 9 publications
4
20
2
3
Order By: Relevance
“…Solares et al considered that successful treatment of FBCA requires complete resection and stated that complete resection requires full exposure of the facial nerve. We recommend making the incision as described by Zhang and Ni et al instead of the traditional “S” or “Y” shaped incision. For type I FBCAs in the present study, a fusiform incision was made, including the infected area in the post‐aurum.…”
Section: Discussionmentioning
confidence: 99%
“…Solares et al considered that successful treatment of FBCA requires complete resection and stated that complete resection requires full exposure of the facial nerve. We recommend making the incision as described by Zhang and Ni et al instead of the traditional “S” or “Y” shaped incision. For type I FBCAs in the present study, a fusiform incision was made, including the infected area in the post‐aurum.…”
Section: Discussionmentioning
confidence: 99%
“…Previous authors have suggested that type II FBCAs exhibit a closer relationship with the facial nerve than type I FBCAs. 6,7 Type II FBCAs are located from the earlobe to the upper neck, but not all type II FBCAs adhere to the facial nerve. In the present study, we divided type II FBCAs into three subtypes based on MRI findings.…”
Section: Discussionmentioning
confidence: 99%
“…Such complications include both temporary and permanent facial nerve palsy. Zhang et al 6 confirmed a close relationship between type II FBCAs and the facial nerve, especially when the fistula opening is located below the mandibular angle. In these patients, the facial nerve may lie more superficially and ascend toward the fistula.…”
Section: Introductionmentioning
confidence: 94%
“…FBCAs are difficult to surgically resect due to their close association with the facial nerve. Complications can include facial nerve palsy/injury, parotid seroma, EAC stenosis [4]. Due to the close association of the facial nerve with type II lesions, it is recommended to have an operative microscope or telescope to avoid injury to the nerve, as well as contrast-enhanced preoperative imaging and intraoperative facial nerve monitoring.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Due to the close association of the facial nerve with type II lesions, it is recommended to have an operative microscope or telescope to avoid injury to the nerve, as well as contrast-enhanced preoperative imaging and intraoperative facial nerve monitoring. In fact, some surgeons in still a water-soluble dye such as methylene blue intraoperatively to help define the anomalous tract [4].…”
Section: Conflicts Of Interestmentioning
confidence: 99%